The Implementation of the Duolingo App in Increasing Students’ Vocabulary Mastery - Nurhayati, Evi; Maman Suryaman (Universitas Pendidikan Ganesha, 2023)
Vocabulary is one of the most essential parts of learning English. One of the mobile applications that can assist in learning English vocabulary is the Duolingo application that one of the most popular applications for English learning. The background of the study is because, for EFL students, there are a bunch of difficulties they have to face while learning vocabulary. This study is aimed to analyze the implementation of Duolingo to enhance vocabulary mastery as media learning English Vocabulary of high school students. This study presented the results of an experimental study investigating the impact of a gamification mobile-assisted language learning application called Duolingo in students’ vocabulary learning The researcher use a quasi-experimental research method. To address this issue, this study investigated the effectiveness of Duolingo by comparing pre-test and post-test scores of control and an experimental class. The results of the implementation of Duolingo use in the experimental class indicated that post-test scores were higher for the experimental group than for the control group and the experimental class showed a quite big improvement.